BACTERIAL DNA EXTRACTION METHOD FOR THE DETECTION OF HELICOBACTER PYLORI FROM HUMAN FECAL SAMPLES - GUAMÁN, JHOAN; BAYAS-MOREJÓN, FAVIAN; BRITO, ELENA; PAREDES, NORMA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The work proposed the implementation of a method of DNA extraction for the detection of the pathogen from 50 stool samples. Methods: A method of DNA extraction with Chelex resin was applied and then detected by conventional polymerase chain reaction (PCR). Results: By PCR, 11 samples were positive for Helicobacter pylori. Conclusions: The Chelex extraction methodology allows obtaining DNA with quality necessary to be detected by PCR, making it a fast methodology for its diagnostic application.